Sex differences in physiological response during incremental test in young long and middle distance runners - Tota, L.; Pilch, W.; Wiecha, S.; Maciejczyk, M. (Journal of Kinesiology and Exercise Sciences, 2012)
Aim of the study. To determine sexual differences in the values of selected physiological measures at two levels of exercise intensity, i.e. at the threshold of decompensated metabolic acidosis and during maximal exercise. The levels of selected physiological measures were expressed in absolute terms and relative to body mass and fat free mass FFM. Material and methods. The study covered 11 male and 16 female subjects at the age of junior and cadet (15-17 years) who specialized in medium and long distance running events. Graded exercise test until fatigue performed on mechanical treadmill was employed to determine the maximal and threshold levels of basic physiological measures. The exercise test was started with a four-minute warm-up, with subjects running at constant speed (male subjects: 9 km · h-1; female subjects: 8 km·h-1) and then the speed was increased every 2 minutes. At the final phase of the test, exercise intensity was increased every minute through changing the slope of the treadmill. The TDMA threshold was determined based on the dynamics of alterations in selected parameters of the respiratory system. Results and conclusions. Intergroup differences in the level of somatic measures are typical of general population within this age range. Global levels of maximal oxygen uptake were at the level of 4.02 ± 0.2 l · min-1 in male subjects and 2.83 ± 0.5 l · min-1 in female subjects. The results obtained by women were at the level of merely 70% of those obtained by men. The levels of this measure relative to body mass were significantly different between the groups (lower in women by 15%), whereas relative values of oxygen uptake at the threshold of decompensated metabolic acidosis did not differ significantly. No significant differences were found in the value of oxygen uptake relative to FFM observed at the level of TDMA and maximal exercise intensity.